Fibrinolytic therapy for thrombosis in cardiac valvular prosthesis short and long term results - Ramos,Auristela I. O. (2003)
OBJECTIVE: To assess the short- and long-term results of the use of streptokinase (SK) for the treatment of thromboses in cardiac valvular prostheses. METHODS: Seventeen patients with cardiac prosthetic thrombosis diagnosed by clinical, echocardiographic, and radioscopic findings underwent fibrinolytic treatment with a streptokinase bolus of 250,000 U followed by 100.000 U/hour. Short- and long-term results were assessed by radioscopy and echocardiography. RESULTS: Of the 17 patients, 12 had mechanical double-disk prostheses (4 aortic, 6 mitral, 2 tricuspid), 4 had single-disk prostheses (2 aortic, 1 mitral, and 1 tricuspid), and 1 had a tricuspid bioprosthesis. The success rate was 64.8%, the partial success rate was 17.6%, and the nonsuccess rate was 17.6%. All patients with a double-disk prosthesis responded, completely or partially, to the treatment. None of the patients with a single-disk prosthesis had complete resolution of the thrombosis. The time of streptokinase infusion ranged from 6 to 80 hours (mean of 56 h). The mortality rate due to the use of streptokinase was 5.8% and was secondary to cerebral bleeding. During streptokinase infusion, 3 (17.6%) embolic episodes occurred as follows: 1 cerebral, 1 peripheral, and 1 coronary. The rethrombosis index was 33% in a mean follow-up of 42 months. CONCLUSION: The use of fibrinolytic agents was effective and relatively safe in patients with primary thrombosis of a double-disk prosthesis. A fatal hemorrhagic complication occurred in 1 (5.8%) patient, and embolic complications occurred in 3 (17.6%) patients. In a mean 42-month follow-up, 67% of the patients were free from rethrombosis.